Adaptive ON-OFF spiking photoreceptor - Degenaar,P; Constandinou,TG; Toumazou,C (Electronics Letters, 2006)
An adaptive spike generator circuit for intelligent vision chips is presented. A pulse frequency modulation spike encoder, capable of providing very high dynamic ranges with power consumption similar to an animal retina, has been developed. The circuit is inspired by the ON-OFF opponency algorithm used by the human eye.